Security Dimension of Zakat: Mitigating Social Unrest and Promoting Sustainable Communities - Abdullahi, Nazifi; Ibrahim, Ibrahim Aminu; Umar, Aliyu Salisu (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2025)
Zakat has been an instrumental in promoting social wellbeing of the underprivileged. Findings have shown that societies with institutionalized zakat systems such as Sudan and Indonesia were able to reduce the poverty rates by up to 15%, and incidents of property crime and violent crime by 20%. This paper studies zakat beyond its apparent potencies in poverty reduction. It focuses on the security dimension of zakat, while exploring it as catalyst for communal security by way of providing financial support to the poor, which ultimately leads to communal security. It seeks to establish relation between zakat and communal security by highlighting its potencies to mitigate social unrest and enhance mutual protection and cooperation among members. Hence, the study addresses a critical gap in the literature by positioning zakat as a multidimensional instrument that corresponds with Sustainable Development Goals (SDGs). The research employs qualitative design to explore the potencies of zakat in mitigating communal insecurity, and also utilizes secondary data for its accessibility, cost-effectiveness and adequacy of existing literature on zakat and social and economic impacts. Data were evaluated to ensure relevance, credibility and reliability, as well as analyzed thematically. The research discovers that, effective management of zakat funds liberates societies from social problems like – social vices, poverty, economic disparities, and unemployment, hence providing social cohesion, financial and communal security which catalyzes for sustainable communities. The study recommends that maximizing the impact of zakat for building sustainable communities requires educating zakat recipients on effective financial management, entrepreneurship, and investment opportunities.